MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI SURAT RESMI KELAS VI SD (The Cooperative Integrated Reading Composition [CIRC] Model to Increase The Student's Learning Result in Bahasa Indonesia Material Formal Letter Discussion in The Sixth Grade of Elementary School) - Nolia Nolia (Sirok Bastra, 2021)
Kemampuan peserta didik dalam materi surat resmi sangat rendah sehingga perlu suatu model pembelajaran yang sesuai untuk mengingkatkan kemampuan tersebut. Penelitian ini bertujuan untuk meningkatkan hasil belajar Bahasa Indonesia materi surat resmi dengan model Cooperative Integrated Reading and Composition (CIRC) pada peserta didik kelas VI semester 2 SD Negeri 5 Manggar. Metode yang digunakan pada penelitian ini adalah penelitian tindakan kelas dengan metode analisis data kuantitatif dan deskriptif. Hasil analisis data kuntitatif, yaitu ketuntasan peserta didik secara klasikal pada kegiatan prasiklus 25%, siklus 1 41,7%, dan siklus 2 91,7%. Sedangkan analisis deskriptif terdapat peningkatan aktivitas positif peserta didik, yaitu bersemangat dan aktif mengikuti proses pembelajaran pada prasiklus 33,3%, siklus 1 75%, dan siklus 2 100%. Senang bertanya kepada guru atupun teman tentang materi yang sedang dipelajari pada prasiklus 25%, siklus 1 58,3%, dan siklus 2 83,3%. Menanggapi pertanyaan guru dengan baik pada prasiklus 25%, siklus 1 50%, dan siklus 2 91,7%. Student's competency in writing the formal letters was very low, so it's necessary to create a learning model that is able to increase the competency. The research aims to increase the learning result in Bahasa Indonesia subject on formal letter material by using cooperative integrated reading and composition to sixth-grade students of SD Negeri 5 Manggar in the second-semester academic year. The action research is chosen as a research method by quantitative and descriptive data analysis Through quantitative analysis result shown students' classical passing grade in the pra cycle is 25% than in the first cycle is 41.7 % and in the second cycle 91.7%. On the other hand, the result of descriptive analysis showed that there were some positive achievements in students' activities such as the level of curiosity and their involvement in the learning process. The achievement can be shown by the improvement of percentage in every cycle like 33.3 % in the pra cycle, 75% in the first cycle, and 100% in the second cycle. The study also impacts the increase of student's asking behavior, in the pra cycle 25%, the first cycle 58.3%, and the second cycle 83.3%. The student's responses to the teacher's questions increases from 25% in the pra cycle to 50% in the first cycle and 91.7% in the second cycle.